Analyzing angular momentum in the takeoff phase of medium-hill ski jumping - Funato, Yuta; Nakashima, Hirotaka; Sakurai, Shinji (Frontiers in Sports and Active Living, 2025)
IntroductionAthletic performance in competitive ski jumping is evaluated based on the aggregate scores of the jump distance and flying style. However, an understanding of how angular momentum influences performance, particularly during the approach to takeoff phases, is lacking. Therefore, this study aimed to quantify the angular momentum during the takeoff motion on a medium hill and to examine the appropriate angular momentum.MethodsThe study participants included 21 jumpers (16 males and five females; height: 1.65 ± 0.09 m; total weight: 54.6 ± 8.9 kg; age: 19.2 ± 6.8 years) performing on a medium hill. The angular momentum of the center of gravity of the jumper + ski system (AMCG) at takeoff was filmed at 200 Hz using a high-speed camera and analyzed in the sagittal plane.ResultsAs a result of confirming the relationship between AMCG at takeoff and jump distance, a significant quadratic approximation curve was obtained, indicating that the value at the apex of the X-axis was 0.0391 s−1 (p < 0.05).DiscussionThis study shows that the appropriate AMCG value at takeoff was approximately 0.0391 s−1. The study findings are expected to contribute to coaching with objective indicators.